Effect of ethylene glycol and its derivatives on the aggregation properties of reactive Orange 13 dye aqueous solution. Issue 57 (16th September 2020) - Qi, Yong; Xie, Ruyi; Yu, Aihong; Bukhari, Mohd Nadeem; Zhang, Liyuan; Cao, Chuangui; Peng, Hui; Fang, Kuanjun; Chen, Weichao
Abstract : The interaction between Orange 13 dye and ethylene glycol and its derivatives was determined by the dispersion force. Abstract : The aggregation behavior of dyes especially in the dyeing and printing of different textile materials is an important phenomenon which affects the process of dye adsorption and diffusion. In order to avoid the aggregation of dyes, scientists are looking for materials which can inhibit the aggregation process by fabricating the dye solution. Organic solvents have found important influence in the aggregation of dye molecules. Therefore, herein, we report the fabrication of reactive orange 13 dye solutions with the aid of ethylene glycol and its derivative organic solvents to investigate the aggregation behavior of dye molecules by UV-vis absorption spectrum, fluorescence spectrum, surface tension, rheological and particle size measurements. IR spectra were performed to understand the effect of hydrogen bonding on the aggregation behavior of dye molecules. Moreover, transmission electron microscopy was also tested to confirm the effect of organic solvents on the surface morphology of dye molecules. The results show that the reactive Orange 13 dye molecules show aggregation in terms of dimeric and multimeric structures at high dye concentrations due to π–π interaction of naphthalene rings. Moreover, on introducing the ethylene glycol and its derivatives, the dye molecules disaggregate by hydrophobic interactions of dye molecules and organic solvents which destroyed the ice-like structure between the dye molecules and the water molecules. Among the three organic solvents, DME solvent caused more disaggregation of reactive Orange 13 dye molecules due to extra hydrophobic methyl groups in its structure. The results also show that the interaction between Orange 13 dyes and ethylene glycol and its derivatives could decrease the surface tension and particle size of the dye, and increase the quantum yield and viscosity. This research will help to understand the aggregation behavior of dyes and help the textile industries to choose the suitable formulations of dye solutions for coloration of different textile substrates via dyeing and printing methods.